Patent Landscape Report : Graphite and its applications. ([World Intellectual Property Organization], 2023)
This WIPO Patent Landscape Report examines global graphite-related patenting activity in the last decade. In addition, the report uses market and business information to assess the current state of graphite technologies and identify innovation hot topics, as well as examining both better-studied areas and the emerging uses of graphite.
Keywords: Patents.; Chemical industry.; Graphite Technologies.; Industries chimiques.; Chemical industry; Patents